2022
DOI: 10.1038/s41598-022-21891-0
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of immune-regulatory proteins C5AR1, CLEC4A and NLRP3 on peripheral blood mononuclear cells in early-stage non-small cell lung cancer patients

Abstract: Changes in gene expression profiling of peripheral blood mononuclear cells (PBMC) appear to represent the host’s response to the cancer cells via paracrine signaling. We speculated that protein expression on circulating T-lymphocytes represent T-lymphocyte trafficking before infiltration into the tumor microenvironment. The possibility of using protein expression on circulating T-lymphocytes as a biomarker to discriminate early-stage non-small cell lung cancer (NSCLC) was explored. Four independent PBMC gene e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…Multiple studies have postulated about the ability of cancer cells to produce cytokine and chemokine-like secretion molecules which affect gene expression changes in blood circulating immune cells, including WBCs, contributing to the progression of various forms of cancer and impacting outcomes 31 34 . Recent works have shown that the levels of mRNA and protein expression of PBMCs exhibited changes in both hepatocellular carcinoma and non-small cell lung cancer 27 , 35 . In line with this previous work, our findings also described the mechanism of cancer cytokine signaling in molecule-regulated gene expression of immune cells in pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have postulated about the ability of cancer cells to produce cytokine and chemokine-like secretion molecules which affect gene expression changes in blood circulating immune cells, including WBCs, contributing to the progression of various forms of cancer and impacting outcomes 31 34 . Recent works have shown that the levels of mRNA and protein expression of PBMCs exhibited changes in both hepatocellular carcinoma and non-small cell lung cancer 27 , 35 . In line with this previous work, our findings also described the mechanism of cancer cytokine signaling in molecule-regulated gene expression of immune cells in pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, CLEC4A is also critical in tumorigenesis. In lung cancer and hepatocellular carcinoma, CLEC4 regulates the infiltration of various immune cells, making it a potential target for novel immunotherapy [ 33 , 34 ]. Recent reports have indicated that TENT5C, an unconventional poly(A) RNA polymerase known for boosting mRNA stability and gene expression, interferes with Plk4 function [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Except for ACSL1, a biomarker associated with ferroptosis, SLC2A3, MMP9, C5AR1, and NLRP3 are all biomarkers associated with pyroptosis. It has been shown that SLC2A3 is co-expressed with MMP9, SLC2A3 is co-expressed with C5AR1, and C5AR1 is co-expressed with NLRP3 ( 33 35 ), and they are all elevated genes in the male IS patient group. Therefore, pyroptosis is the primary form of cell death determining the course of IS in male patients.…”
Section: Discussionmentioning
confidence: 99%